Asymptotic integration of singularly perturbed systems of hyperbolic-type partial differential equations with degeneration - Samusenko, P. F. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
An asymptotic solution of the first boundary-value problem for a linear singularly perturbed system of hyperbolic-type partial differential equations with degeneration is constructed.